Injectable: In situ forming hydrogel gene depot to improve the therapeutic effect of STAT3 shRNA - Kim, Da Yeon; Ju, Hyeon Jin; Kim, Jae Ho; Choi, Sangdun; Kim, Moon Suk (Biomaterials Science, 2021)
Down-regulation of the signal transducer and activity of transcription 3 (Stat3) plays a crucial role in suppression of many solid tumors. Intratumoral injection of a gene carrier applying Stat3-small hairpin RNA (St3-shRNA) is a potential therapeutic strategy. To our knowledge, this is the first report of the intratumoral injection of St3-shRNA using a gene carrier. We herein designed biodegradable (methoxy)polyethylene glycol-b-(polycaprolactone-ran-polylactide) copolymer (MP) derivatized with a spermine group with cationic properties at the pendant position of the MP chain (MP-NH2). The designed MP-NH2 can act as a gene carrier of St3-shRNA by forming an electrostatic complex with cationic spermine. This can increase the stability of the complexes because of protection of PEG in biologic environments and can exhibit a sol-gel phase transition around body temperature for the formation of intratumorally injected MP-NH2 hydrogel depot for St3-shRNA. MP-NH2 was observed to completely condense with St3-shRNA to form St3-shRNA/MP-NH2 complexes. These complexes were protected for a relatively long time (≥72 h) from external biologic molecules of the serum, DNase, and heparin. St3-shRNA/MP-NH2 complexes in in vitro tumor cell experiments can enhance transfection of St3-shRNA, correspondingly enhance Stat3 knockdown efficiency, and inhibit tumor cell growth. St3-shRNA/MP-NH2 complexes and St3-shRNA/MP-NH2 complex-loaded hydrogel were intratumorally injected into the tumor as new efficient delivery carriers and depots of St3-shRNA. The intratumoral injection of St3-shRNA/MP-NH2 complexes and St3-shRNA/MP-NH2 complex-loaded hydrogel showed effective anti-tumor effect for an extended period of time due to the effect of Stat3 knockdown. Collectively, the development of MP-NH2 as a carrier and depot of St3-shRNA provides a new strategy for St3-shRNA therapy through intratumoral injection with high efficacy and minimal adverse effects.
Keywords: Biologic environments; Delivery carriers; Electrostatic complexes; Intratumoral injection; Signal transducers; Sol-gel phase transition; Therapeutic effects; Therapeutic strategy; Hydrogels; Injections; Polyethylene Glycols; Polymers; RNA, Small Interfering; Transfection